2020
DOI: 10.1101/2020.09.09.20191353
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Covid-19 epidemic curve in Brazil: A sum of multiple epidemics, whose income inequality and population density in the states are correlated with growth rate and daily acceleration

Abstract: Introduction: Recently, we demonstrated that the polynomial interpolation method can be used to accurately calculate the daily acceleration of cases and deaths by Covid-19. The acceleration of new cases is important for the characterization and comparison of epidemic curves. The objective of this work is to measure the diversity of epidemic curves and understand the importance of socioeconomic variables in the acceleration, peak cases and deaths by Covid-19 in Brazilian states. Methods: This is an ecological s… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 6 publications
1
2
0
Order By: Relevance
“…We also observed a positive association between the GINI index and mortality due to COVID-19, which is similar to the current literature [65][66][67]. Interestingly, studies also reported an association between the GINI index and the incidence of COVID-19 cases [68,69].…”
Section: Discussionsupporting
confidence: 91%
“…We also observed a positive association between the GINI index and mortality due to COVID-19, which is similar to the current literature [65][66][67]. Interestingly, studies also reported an association between the GINI index and the incidence of COVID-19 cases [68,69].…”
Section: Discussionsupporting
confidence: 91%
“…The data from Brazilian studies (46)(47)(48)(49)(50)(51)(52) suggest that pandemic were highly heterogeneous in the country, with rapid growth in North and Northeast regions, and slow progression in the South and Center-West regions. These data demonstrate the impact of differences in demographics, urban infrastructure and income on the infection spreading and seroprevalence, emphasizing health inequality (62,63).…”
Section: Discussionmentioning
confidence: 72%
“…As a result bias correction factors may need to be derived. Interactions with other epidemics may also introduce bias in countries that are experiencing other outbreaks beyond COVID-19, such as Brazil [52].…”
Section: Discussionmentioning
confidence: 99%